Lead like Jesus : lessons from the greatest leadership role model of all times - Blanchard, Kenneth H. (W Pub. Group, 2005)
"Learn how to lead like Jesus, whether in the home, the church, the community, or the marketplace; moving not only from success to significance but taking a step beyond significance--surrender"--Provided by publisher.